2015
DOI: 10.1136/jramc-2015-000541
|View full text |Cite
|
Sign up to set email alerts
|

Impact of personal protective equipment on clinical output and perceived exertion

Abstract: Despite acclimatisation and proactive clinical tasking, HCPs in the EVDTU experienced significantly greater rates of weight loss and perceived exertion scores during the hottest times of the day. These findings should be considered by those planning healthcare facilities for future humanitarian missions where HCPs will provide clinical care in full PPE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 4 publications
(3 reference statements)
0
19
1
1
Order By: Relevance
“…Additional follow-up studies should explore why environmental temperatures affect EVD case fatality to better disentangle the impacts on patient physiology vs. inhibition of care delivery. The threat of overheating and fluid loss for EVD providers in full PPE limits the amount of time that can be spent caring for patients [12]. It is possible that on days with relatively higher ambient temperatures, the amount of time providers can spend with patients is further limited, and that this could negatively impact patient outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additional follow-up studies should explore why environmental temperatures affect EVD case fatality to better disentangle the impacts on patient physiology vs. inhibition of care delivery. The threat of overheating and fluid loss for EVD providers in full PPE limits the amount of time that can be spent caring for patients [12]. It is possible that on days with relatively higher ambient temperatures, the amount of time providers can spend with patients is further limited, and that this could negatively impact patient outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Maynard et al . found that EVD providers in full PPE lose 0.014 kg/min body weight in midday hours from fluid loss . Patients are also exposed to intense temperatures inside of ETUs, often structures built of plastic sheeting and exposed to long hours of direct sunlight due to the West African climate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The heat and humidity in West Africa make wearing protective equipment uncomfortably hot and physiologically stressful, with staff feeling physically stressed and typically losing up to a litre of sweat during each trip into the red zone. 9 On top of this, the risk of becoming infected with Ebola was clearly a very real one, with multiple doctors and nurses infected in 2014 in hospitals in North America and Europe whilst treating patients who were known to be harbouring the virus. 10 There was significant concern in the health-care community that bringing infected UK health-care workers back to the UK to be treated would jeopardize the safety of staff in the NHS and risk disrupting the running of already full critical care units.…”
mentioning
confidence: 99%
“…They also advocate its use in other areas, including the following: during cardiopulmonary resuscitation, in the department of emergency medicine, in the intensive care unit, in the prehospital setting, and as an important step in the difficult airway algorithm. [7][8][9] Manufacturers hardly put efforts into verification of the correct placement or positioning of the device in situ after insertion. Contrary to the insertion of a tracheal tube, which is guided to the trachea under (in)direct vision of a (video)laryngoscope, the insertion of a SAD is virtually a 'blind' technique, whereby one relies on the practitioner's skills to insert the device correctly into the hypopharynx.…”
mentioning
confidence: 99%